Family Involvement And Academic Self Efficacy as a Factors in Childrens Academic Engagement - Nurmina, Nurmina (COUNS-EDU: The International Journal of Counseling and Education, 2017)
The main goal of the present study is to examine the effect of family involvement and academic self efficacy toward children academic engagement. Sample of this research 97 children from 5rd to 6th grade of elementary school. Data collection tool used was questionaire form of academic engagement scale (35 items), family involvement scale (28 items), and academic self efficacy scale (40 items). Based on the analysis of research data, it was found that the obtained R square value of 0.35 with a significance level of p<0.01. It can be concluded that there are significant effect of family involvement and academic self efficacy toward children academic engagement. In general, we found the positive impact of students academic self-efficacy and parents involvement on students school engagement. But their impact differ in the respondent, their parents personal and their parents involvement characteristics also. As an example, gender status, specifically being as female, made their academic engagement better.